Emerging roles of interactions between ncRNAs and other epigenetic modifications in breast cancer - Xie, Junyuan; Gan, Li; Xue, Bingjian; Wang, Xinxing; Pei, Xinhong (Frontiers in Oncology, 2023)
Up till the present moment, breast cancer is still the leading cause of cancer-related death in women worldwide. Although the treatment methods and protocols for breast cancer are constantly improving, the long-term prognosis of patients is still not optimistic due to the complex heterogeneity of the disease, multi-organ metastasis, chemotherapy and radiotherapy resistance. As a newly discovered class of non-coding RNAs, ncRNAs play an important role in various cancers. Especially in breast cancer, lncRNAs have received extensive attention and have been confirmed to regulate cancer progression through a variety of pathways. Meanwhile, the study of epigenetic modification, including DNA methylation, RNA methylation and histone modification, has developed rapidly in recent years, which has greatly promoted the attention to the important role of non-coding RNAs in breast cancer. In this review, we carefully and comprehensively describe the interactions between several major classes of epigenetic modifications and ncRNAs, as well as their different subsequent biological effects, and discuss their potential for practical clinical applications.